2015
DOI: 10.1002/lary.25788
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of swallowing mechanics underlying impaired epiglottic inversion

Abstract: Objective Determine swallowing mechanics associated with the first and second epiglottic movements, that is, movement to horizontal and full inversion respectively, in order to provide a clinical interpretation of impaired epiglottic function. Study Design Retrospective cohort study. Methods A heterogeneous cohort of patients with swallowing difficulties was identified (n=92). Two speech-language pathologists reviewed 5ml thin and 5ml pudding videofluoroscopic swallow studies per subject, and assigned epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Further, previous studies have shown that, although there is likely a correlation between hyoid movement and epiglottic inversion, hyoid excursion is not necessary for epiglottic inversion. Impaired epiglottic inversion is primarily caused by reduced elevation and reduced tongue base retraction but not by reductions in hyoid movement . It is thought that the pharyngeal longitudinal muscles play a role in inversion of the epiglottis as well as closure of the laryngeal aperture when functioning with the muscular components of the aryepiglottic folds .…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies have shown that, although there is likely a correlation between hyoid movement and epiglottic inversion, hyoid excursion is not necessary for epiglottic inversion. Impaired epiglottic inversion is primarily caused by reduced elevation and reduced tongue base retraction but not by reductions in hyoid movement . It is thought that the pharyngeal longitudinal muscles play a role in inversion of the epiglottis as well as closure of the laryngeal aperture when functioning with the muscular components of the aryepiglottic folds .…”
Section: Discussionmentioning
confidence: 99%
“…15 Relevant to this study, CASM can analyze the movement of pharyngeal muscle groups and structures that may cause measurable changes in the HRPM UES pressure profile. 15 Relevant to this study, CASM can analyze the movement of pharyngeal muscle groups and structures that may cause measurable changes in the HRPM UES pressure profile.…”
Section: Introductionmentioning
confidence: 99%
“…These landmarks can be reliably obtained from imaging data including hyoid movement, laryngeal elevation, tongue base retraction, pharyngeal shortening, and head and neck posture (Figure 1) [37, 38]. Configurations of coordinates represent the interaction of multiple muscle groups underlying pharyngeal swallowing mechanics as these landmarks are displaced.…”
Section: Introductionmentioning
confidence: 99%